INFLUENCE OF EXPORT LEASE EXTRACT AND AZOLLA TOWARDS WEIGHT AND CARRYS PERCENTAGE OF ITEM CARE - Ethelburg Rafael Warin Hera; Aju Tjatur Nugroho Krisnaningsih; Dyah Lestari Yulianti (Jurnal Sains Peternakan, 2016)
ABSTRACT The purpose of this study was to determine the effect of the leaf extract beluntas and Azolla on carcass weight and carcass percentage broiler ducks. This study uses field research by using a completely randomized design (CRD), which consists of 4 treatments with 4 replicates and each treatment using 12 broiler ducks. Aspects observed in this study is the carcass weight and carcass percentage on broiler ducks. From the results of this study showed the highest body weight contained in P0B treatment for only 1400 grams, while the lowest was in the weight of 1000 grams P3D. This difference is due to the degree of weight gain with different consumption. From these results it can be seen that the leaf extract beluntas and Azolla show that there is a real impact on carcass weight. Because at the time of treatment the first week to the second week pobud remaining feed, whereas in the second week of treatment until the third week of feed pobud run out. This difference is due to the degree of weight gain and consumption are different. Based on the results of analysis of variance is known that the use of leaf extracts beluntas and Azolla significantly affect carcass percentage of 40-day-old broiler ducks. The real effect of this is due to the use of extracts of leaves beluntas and each treatment as much as P1 beluntas (0.18 kg) and P1 azolla (1.02 kg), P2 beluntas (0.12 kg) and P2 azolla (1.08 kg), P3 beluntas (0.06 kg) and P3 azolla (1.14 kg), in the diet is not giving effect to the carcass percentage. Keywords : Broiler ducks, beluntas, azolla, carcass weight, carcass percentage